Effect of row skipping in tree cotton (Gossypium arboreum) on efficacy of chemical control of spotted bollworms (Earias vittella and E. insulana) and pink bollworm (Pectinophora gossypiella) - SINGH, JAI; SANDHU, B S (The Indian Journal of Agricultural Sciences, 2013)
The effect of skipping a row at sowing to provide a path for spray operation was studied on the efficacy of chemical control of bollworms on 'LD 327' tree cotton (Gossypium arboreum L.) during 1992 and 1993. Skipping the fourth, fifty, sixty and seventh rows was compared with no skipping at 3 locations during 1992. However, skipping of fourth row was omitted in subsequent trials in 1993. Average data kof locations and years showed that skipping every fifth row at sowing proved significantly better than no skipping as well as skipping of sixth and seventh rows in lowering the incidence of spotted bollworms (Earias vittella fabr. and E. insulana Boisd.) and pink bollworm (Pectibophora gossypiella Saund.) as well as stained seed-cotton. Besides compensating for missing row, this treatment also incresed the seed-cotton yield by 15.2 and 20.1% during 1992 and 1993 respectively.